Nutrient Sensing and Redox Balance: GCN2 as a New Integrator in Aging. (22nd May 2019) - Falcón, Paulina; Escandón, Marcela; Brito, Álvaro; Matus, Soledad
Abstract : Aging is a complex process in which the accumulation of molecular, cellular, and organism dysfunction increases the probability of death. Several pieces of evidence have revealed a contribution of stress responses in aging and in aging-related diseases, in particular, the key role of signaling pathways associated to nutritional stress. Here, we review the possible interplay between amino acid sensing and redox balance maintenance mediated by the nutritional sensor general control nonderepressive 2 (GCN2). We discuss this new dimension of nutritional stress sensing consequences, standing out GCN2 as a central coordinator of key cellular processes that assure healthy homeostasis in the cell, raising GCN2 as a novel interesting target, that when activated, could imply pleiotropic benefits, particularly GCN2 intervention and its new unexplored therapeutic role as a player in the aging process.